2004
DOI: 10.1081/drt-200040014
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Drying of Porous Materials

Abstract: Experimental results on microwave drying of the porous particles exposed to air stream at 40 C are presented. The temperature and moisture distribution inside a particle were measured for gypsum spheres of 9, 18, 28, and 38 mm. The mass reduction was monitored during the drying process. The rate of drying and changes in temperature and moisture profiles for different drying conditions were analyzed and compared with the ones for convective drying.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 14 publications
0
21
0
Order By: Relevance
“…Therefore, at the beginning of the process where the moisture content of the sample exceeds 83.5 % wet basis (5.08 kg water/kg dry matter), the sample will absorb more microwave power causing a very high internal heat generation which in turn produces higher diffusion and thus higher drying rate. As drying proceeds, moisture content within the sample decreases and thus decreasing the absorption of microwave power (Araszkiewicz et al 2004;Darvishi et al 2013;Soysal et al 2006). Besides, the energy efficiency is increasing with increasing microwave power and decreasing slice thickness and microwave power is more effective on efficiency (P ≤ 0.05, Table 2).…”
Section: Energy Analysesmentioning
confidence: 94%
“…Therefore, at the beginning of the process where the moisture content of the sample exceeds 83.5 % wet basis (5.08 kg water/kg dry matter), the sample will absorb more microwave power causing a very high internal heat generation which in turn produces higher diffusion and thus higher drying rate. As drying proceeds, moisture content within the sample decreases and thus decreasing the absorption of microwave power (Araszkiewicz et al 2004;Darvishi et al 2013;Soysal et al 2006). Besides, the energy efficiency is increasing with increasing microwave power and decreasing slice thickness and microwave power is more effective on efficiency (P ≤ 0.05, Table 2).…”
Section: Energy Analysesmentioning
confidence: 94%
“…Following moisture reduction, the energy absorbed by the product decreased and the reflected power increased (Araszkiewicz et al, 2004;Mousa and Farid, 2002;Soysal et al, 2006). For this reason, it was observed that as the microwave power increased the energy losses increased, in other words, the values of microwave energy efficiency decreased.…”
Section: Model Name Model Referencesmentioning
confidence: 89%
“…Datta 1990, Metaxas & Meredith 1983) that describe how the problem of temperature distribution inside the heated material is connected with its shape. The specific case takes place during microwave-assisted drying of a small sphere, which is supposed to act like a lens and focus the electromagnetic waves inside (Schlunder 1993;Araszkiewicz et al 2004;Remmen et al 1996). In this particular case, the temperature maximum appears to be at the geometrical centre of the particle.…”
Section: Volumetric Heatingmentioning
confidence: 98%